1980
DOI: 10.1016/0304-3959(88)90009-7
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of auricular diagnosis: The somatotopic mapping of musculoskeletal pain at ear acupuncture points

Abstract: The present study was designed to experimentally evaluate the claims by French and Chinese acupuncturists that a somatotopic mapping of the body is represented upon the external ear. According to this system of diagnosis, areas of the auricle where there is increased electrical conductivity and heightened tenderness to touch correspond to specific areas of the body where there is some pathological condition. The hypothetical map of different bodily regions appears on the external ear as an inverted fetus, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
7

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 20 publications
1
72
0
7
Order By: Relevance
“…Neither the Ryodoraku nor the Voll machines have been validated with a controlled study. In fact, although measurement of ear resistance has been claimed to correlate 72.5% of the time with Western diagnosis [37], a carefully controlled study by Melzack and Katz [38] found no consistent difference in conductance between acupoints and nearby non-acupoints in patients with chronic pain.…”
Section: Skin Resistancementioning
confidence: 99%
“…Neither the Ryodoraku nor the Voll machines have been validated with a controlled study. In fact, although measurement of ear resistance has been claimed to correlate 72.5% of the time with Western diagnosis [37], a carefully controlled study by Melzack and Katz [38] found no consistent difference in conductance between acupoints and nearby non-acupoints in patients with chronic pain.…”
Section: Skin Resistancementioning
confidence: 99%
“…The reason for this is most likely the immediate vicinity of the ramus auricularis to the well-known ear acupuncture point "shen-men", which is also known as "heavenly gate" [26]. Traditional Chinese medicine in particular, has substantial data indicating that acupuncture of the "shenmen" point is associated with an improvement of complaints in case of anxiety, stress, depression, insomnia, pain, as well as addiction and detoxifi cation [27,28]. Therefore, it would have been interesting to include a third group, without any acupuncture, as a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The needle was placed either (A) in the vagus area, or (B) in the upper ear near the helix, as shown in Figure 1. This has been defined as the most appropriate place for a control ACUPUNCTURE IN MEDICINE DECEMBER 1999 VOL 17 (2) …”
Section: Methodsmentioning
confidence: 99%